Cleaning of dried fish - Mumbai Archive Project Team (Jio Institute, 2024)
Men from the Koli community typically venture out to sea in traditional fishing boats to catch fish, shrimp, crabs, and other marine species. The damaged and unsold fish are bought by Koli women to make dried fish, which is a valuable source of income for many Koli families.